Oral Ashitaba Aeaves (Angelica keiskei) Extract Prevented The Increase of Tyrosinase Levels and Total Melanin in The Ultraviolet BExposed Guinea Pig (Cavia porcellus) Skin - Meiny Linda Setiawan; Wimpie Pangkahila; Anak Agung Gede Putra Wiraguna (Fakultas Kedokteran Universitas Udayana, 2020)
Introduction: UVB rays stimulate the tyrosinase which activates the biosynthesis of melanin and cause skin aging characterized by hyperpigmentation. Ashitaba is a plant rich of chalcone, a flavonoid compound with tyrosinase inhibitor activity. This study aimed to prove that oral Ashitaba (Angelica keiskei) extract prevented the elevation of tyrosinase levels and total melanin in the UVB-exposed guinea pig (Cavia porcellus) skin. Methods: This study used randomized posttest only control group design. The subjects were guinea pigs (Cavia porcellus), male, healthy, local strains, aged 3-4 months, weighing 300-350 grams, one hybrid, which were divided into 2 groups (n = 18). The first group was the control group (treatment with exposure to ultraviolet B and placebo), the second group was the treatment group (treatment with exposure to ultraviolet B and oral Ashitaba leaves extract of 25 mg/kgBB). After 2 weeks of treatment, tyrosinase level was examined by the ELISA method, while the amount of melanin was examined for MassonFontana staining. Results: The mean tyrosinase level in the control group after 2 weeks of treatment was higer (30.64 ± 4.19ng/ml) than on the treatment group (11.47 ± 0.62ng/ml) with (p<0.05). In addition, the average number of melanin in the control group was also higer (19.05 ± 2.53%) than the treatment group (1.85 ± 0.84%) (p <0.05). Conclusion: Based on the results of this study, it can be concluded that oral Ashitaba (Angelica keiskei) extract prevented the increase of tyrosinase levels and total melanin in the UVB-exposed guinea pig (Cavia porcellus) skin.